2009
DOI: 10.1128/aac.01550-07
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Polyanionic Microbicides Inhibit Human T-Cell Lymphotropic Virus Type 1 Receptor Interactions, Cell-Free Infection, and Cell-Cell Spread

Abstract: The human T-cell lymphotropic virus type 1 (HTLV-1) is the cause of adult T-cell leukemia and inflammatory diseases including HTLV-1-associated myelopathy/tropical spastic paraparesis. HTLV-1 can be transmitted through sexual contact, mother-to-child transmission, and exposure to contaminated blood. Microbicides are agents that interfere with microbial infectivity at mucous membranes, and candidates are under development for use against sexually transmitted viruses such as human immunodeficiency virus type 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Antibodies and peptides that block LFA/ICAM and MAC-1/JAM C interactions and sulfated polysaccharides inhibit attachment of leukocytes to epithelial cells and, therefore, could inhibit cell-associated HIV transmission [285287]. ICAMs are also important components of viral synapses; therefore, ICAM blockers could also block this cell-associated HIV transmission mechanism.…”
Section: Clinical Approaches To Blocking Cell-associated Hiv Transmismentioning
confidence: 99%
“…Antibodies and peptides that block LFA/ICAM and MAC-1/JAM C interactions and sulfated polysaccharides inhibit attachment of leukocytes to epithelial cells and, therefore, could inhibit cell-associated HIV transmission [285287]. ICAMs are also important components of viral synapses; therefore, ICAM blockers could also block this cell-associated HIV transmission mechanism.…”
Section: Clinical Approaches To Blocking Cell-associated Hiv Transmismentioning
confidence: 99%
“…Studies on candidate topical microbicides suggest that these agents might reduce HTLV-1 sexual transmission 93 and reduce circulating proviral loads without affecting host immune systems; topical microbicides are potential therapeutic agents for the prevention and treatment of HTLV-1-associated diseases 95 .…”
Section: A Decrease In Htlv-1 Viral Shedding and A Reduction In Spreamentioning
confidence: 99%
“…Additionally, HTLV-1 antiserum, which contains high titers of anti-Env neutralizing antibodies, was a potent inhibitor in most of the assays, indicating that neutralizing antibodies in patient sera might play an important role in protection against HTLV-1 transmission, particularly if the antibodies are also at high titers in vaginal secretions. The presence of these antibodies might help limit HTLV-1 transmission via cervicovaginal secretions 93 .…”
Section: A Decrease In Htlv-1 Viral Shedding and A Reduction In Spreamentioning
confidence: 99%
“…In animal experiments, it was reported that the administration of HTLV-1 antibody (Kuo et al, 2011;Fujii et al, 2016;Murakami et al, 2017) and the use of polyanionic microbicides are effective in preventing MTCT (Romer et al, 2009), but they are not ready for human use yet.…”
Section: Preventive Measures Other Than Feeding Methodsmentioning
confidence: 99%